2018
DOI: 10.11648/j.fem.20180401.13
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Multidrug Resistant and Shiga Toxin Producing <i>Escherichia coli</i> (STEC) From Apparently Healthy Broilers in Jessore, Bangladesh

Abstract: The research work was undertaken for detection and determination of antibiogram profile of Escherichia coli (E. coli) that produce Shiga toxin from apparently healthy broilers (n=8) from different commercial farms of Jessore, Bangladesh. Broiler cloacal swabs (n=8) were collected by inserting the sterile swab stick in the cloacae of broiler and inoculated into peptone water for enrichment for 24 hours at 37°C. Enriched culture was streaked onto Eosin Methylene Blue (EMB) agar for isolation of pure bacterial cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In this study, we isolated and identified STEC strains with a multidrug resistance pattern from the cloacal contents and carcasses of broilers. Previous reports support our findings (Momtaz & Jamshidi, 2011;Runa et al, 2018). Alonso et al (2012), detected a higher frequency of STEC pathotypes in carcasses, when compared to the frequency in cloaca.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we isolated and identified STEC strains with a multidrug resistance pattern from the cloacal contents and carcasses of broilers. Previous reports support our findings (Momtaz & Jamshidi, 2011;Runa et al, 2018). Alonso et al (2012), detected a higher frequency of STEC pathotypes in carcasses, when compared to the frequency in cloaca.…”
Section: Resultssupporting
confidence: 92%
“…Among E. coli pathotypes, Shiga toxin-producing Escherichia coli (STEC) is known to cause severe episodes of diarrhea that can progress to systemic complications (Pèrez-Cruz et al, 2017). Broiler chickens and derived products are reservoirs of this pathotype (Alonso, Lucchesi, Rodríguez, Parma, & Padola, 2012;Doregiraee et al, 2016;Momtaz & Jamshidi, 2011;Runa, Lijon, & Rahman, 2018), playing an important role as source of transmission to humans. Shiga toxin (STX) is the main virulence factor of STEC strains.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli belongs to family Enterobacteriaceae which is Gram-negative, rod-shaped and facultative anaerobic. E. coli is widely found in the gastrointestinal systems of birds (Runa et al, 2018), it serves to prevent the colonization of pathogenic bacteria in the intestine, aids in digestion, and can benefit their hosts by creating trace amounts of vitamins B12 and K2, it is a harmful to both humans and poultry to some level (Hudault et al, 2001). Although the majority of E. coli isolates are not harmful, their presence indicates that feces have contaminated food.…”
Section: Introductionmentioning
confidence: 99%